New Technology Prospect of LTE System - Zhen Shao; Min Cao; Yiming Li (Dianxin kexue)
In response to meet the need of immense amounts of network traffic，brought by mobile internet，a new network form of the heterogeneous network should be introduced into 4G network，and a multi-network inte11igent interworking of “mobile smart pipe”is to be built，in order to firstly make a breakthrough on network architecture. New technologies as LTE wireless hierarchica1 networking（HetNet），inter ce11 interference coordination，and LTE and WLAN networks inte11igent integration based on SaMOG（S2a Mobility based on GTP），ANDSF，combined with 3GPP standardization progress were introduced，and prospects of 4G technology were given.